Recent Publications (Quarterly Journal of Economics, 1953)
Recent Publications Get access The Quarterly Journal of Economics, Volume 67, Issue 1, February 1953, Pages 144–147, https://doi.org/10.1093/qje/67.1.144 Published: 01 February 1953